Team Rwanda: will Africans dominate professional road cycling in the future? - Nyakayiru, J.; Verdijk, L. B.; Cermak, N. M.; van Loon, L. J. C. (British Journal of Sports Medicine, 2017)
Kenya-born cyclist Chris Froome has once again won the Tour de France. Although the current title-holder is not a native Kenyan, some believe that the multiday stage race will one day be won by a cyclist with East-African roots. In 2015, the world got a glimpse of what might become a common sight in future editions of the Tour. The latest edition of the event introduced MTN-Qhubeka (currently known as Team Dimension Data for Qhubeka) as its first professional African cycling team ever to participate. The team's Eritrean cyclist Daniel Teklehaimanot exceeded all expectations by becoming the first native African to win the King of the Mountains classification of Critérium du Dauphiné, as well as by claiming the polka dot jersey in the early stages of the tour a few weeks later. But are riders such as Daniel Teklehaimanot and his Rwandan team-mate Adrien Niyonshuti the first of many native Africans who will soon be dominating professional road cycling? Besides the fact that most African countries lack a well-embedded cycling culture, with the exception of Daniel Teklehaimanot's Eritrea, do native African cyclists have what it takes to become elite cyclists?